2005
DOI: 10.2337/diacare.28.4.856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Use of Antiretroviral Agents on Serum Insulin Levels of the Newborn Infant

Abstract: OBJECTIVE -The aim of this study was to investigate the effect of antiretroviral drugs on neonatal serum insulin levels. RESEARCH DESIGN AND METHODS-A prospective study was conducted on 57 pregnant women divided into three groups: the zidovudine (ZDV) group, HIV-infected women taking ZDV (n ϭ 20); the triple treatment group, HIV-infected women taking triple antiretroviral agents ZDV ϩ lamivudine ϩ nelfinavir (n ϭ 25); and the control group, pregnant women considered normal from a clinical and laboratory standp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…It has been suggested that limited transfer of protease inhibitors may result from their high degree of plasma protein binding and their backwards transport through P-glycoprotein, largely expressed in the placenta [7]. Although there have been few studies analyzing adverse metabolic and biochemical effect of maternal ARV drugs on infant health [8], there have been no reports of the hepatic parameters of newborn infants during the immediate postnatal period [3].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that limited transfer of protease inhibitors may result from their high degree of plasma protein binding and their backwards transport through P-glycoprotein, largely expressed in the placenta [7]. Although there have been few studies analyzing adverse metabolic and biochemical effect of maternal ARV drugs on infant health [8], there have been no reports of the hepatic parameters of newborn infants during the immediate postnatal period [3].…”
Section: Discussionmentioning
confidence: 98%
“…While our data are reassuring, we emphasize the need for careful monitoring for hepatotoxicity after initiation of antiretroviral therapy. Follow-up is still limited and needs to be continued into adulthood before it can be concluded that there is no potential toxicity of maternal ARV treatment [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…Dos efeitos fetais indesejáveis referentes ao uso dos inibidores da protease, os mais relatados são a prematuridade e a restrição de crescimento intra-útero 21,22 , mas existem discordâncias 23 . Recentemente, foi relatada também a ocorrência de insulinopenia neonatal em crianças nascidas de mães que utilizaram estes fármacos durante a gravidez 24 .…”
Section: Identificação De Gestantes Portadoras Do Hiv-1unclassified
“…• Glucose intolerance and gestational diabetes risk may be increased among women on highly active antiretroviral therapy (HAART), particularly in those receiving protease inhibitors, and reduced serum insulin levels have been reported in HAART-exposed newborns [104][105][106][107] Lactic acidosis…”
Section: Metabolic Complicationsmentioning
confidence: 99%